Effectiveness of Regional Policies in Reducing Stunting in South Buru Regency - Nuraida Masbait; Maryam Sangadji; Dientje Rumerung (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Stunting is a human resource development issue that remains a serious challenge in various regions, including South Buru Regency. This study aims to analyze the effectiveness of regional policies in reducing stunting prevalence in South Buru Regency by examining the regional context, demographics, and socioeconomic conditions, as well as policy implementation. This study uses a descriptive qualitative approach. Data were obtained through secondary data sourced from official publications of the Central Statistics Agency, in addition to local government reports, policy documents, and reports from related agencies in the health and social development sectors. and primary data from interviews. Data analysis techniques were carried out through descriptive and interpretative analysis by examining the relationship between policies, health indicator achievements, and regional structural conditions. The study results show that despite improvements in several development indicators, such as the Human Development Index and regional economic growth, stunting prevalence in South Buru Regency remains influenced by various structural factors. Geographical factors, limited access to maternal and child health services, high poverty rates, and an economic structure dominated by the primary sector are key obstacles to achieving optimal policy outcomes. Furthermore, the implementation of stunting reduction policies has not been fully effective and equitable across regions and has not fully reached the most vulnerable groups. This study concludes that the effectiveness of stunting reduction policies in South Buru Regency remains partial and requires strengthening cross-sectoral coordination, equitable distribution of basic services, and policy adjustments to the characteristics of the island region. Therefore, more integrated, sustainable, and locally based policies are needed to support accelerated stunting reduction and improve the quality of human resources in South Buru Regency